2016
DOI: 10.1007/s11051-016-3461-7
|View full text |Cite
|
Sign up to set email alerts
|

How reliably can a material be classified as a nanomaterial? Available particle-sizing techniques at work

Abstract: Currently established and projected regulatory frameworks require the classification of materials (whether nano or non-nano) as specified by respective definitions, most of which are based on the size of the constituent particles. This brings up the question if currently available techniques for particle size determination are capable of reliably classifying materials that potentially fall under these definitions. In this study, a wide variety of characterisation techniques, including counting, fractionating, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 69 publications
3
82
0
2
Order By: Relevance
“…Number weighted particle size distributions are currently not measurable with standardised methods, and estimates suffer from the assumption that SAS aggregates are spherical particles, which is inaccurate in the case of E 551. From the results of a recent study within the EU FP7-funded NanoDefine project (http://www.nanodefine.eu/) using several available particle sizing techniques, it has been concluded that “…the determination of the smallest external dimension remains challenging (if possible at all) for several classes of morphology, e.g., for three-dimensional aggregates…” (Babick et al 2016). In this study, a stabilised suspension of fumed silica particles (colloidal silica) was used, which must not to be confused with E 551.…”
Section: Discussionmentioning
confidence: 99%
“…Number weighted particle size distributions are currently not measurable with standardised methods, and estimates suffer from the assumption that SAS aggregates are spherical particles, which is inaccurate in the case of E 551. From the results of a recent study within the EU FP7-funded NanoDefine project (http://www.nanodefine.eu/) using several available particle sizing techniques, it has been concluded that “…the determination of the smallest external dimension remains challenging (if possible at all) for several classes of morphology, e.g., for three-dimensional aggregates…” (Babick et al 2016). In this study, a stabilised suspension of fumed silica particles (colloidal silica) was used, which must not to be confused with E 551.…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding corresponds to agglomerates of a few to hundreds of pristine n-CuPc fragment particles in RPMI, whereas the fragment particles were nearly individualized with a low level of agglomeration, because their size in medium corresponded well to their size directly after aerosol generation. For example, the AUC analysis showed that the size of frag n-CuPc in RPMI media (1.02 μm) is similar to their size directly after aerosol generation (1.57 μm) if both are compared in the same metrics (number), using the well-established metrics conversion of AUC (Babick et al, 2016). Interestingly, the serum tends to reduce agglomeration of the pristine n-CuPc, but increase agglomeration of the fragments.…”
Section: Characterization Of Pristine N-cupc and Sanding Fragments Inmentioning
confidence: 99%
“…Most MTs that reliably work in the relevant size range (e. g. AC or DLS, cf. [10]) intrinsically determine size distribution that are not numberweighted, for which reason conversion becomes an integral part in data analysis [11,12].…”
Section: Introductionmentioning
confidence: 99%